2020
DOI: 10.1001/jamanetworkopen.2019.19615
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parity and Breastfeeding With Risk of Early Natural Menopause

Abstract: IMPORTANCE Pregnancy and breastfeeding prevent ovulation and may slow the depletion of the ovarian follicle pool. These factors may lower the risk of early menopause, a condition associated with increased risk of cardiovascular disease and other adverse health outcomes. OBJECTIVE To examine the association of parity and breastfeeding with the risk of early menopause. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study within the Nurses' Health Study II cohort (1989-2015) included premenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
7
33
1
Order By: Relevance
“…In a prospective cohort study that included 108 887 women, risk of early menopause was lowest among those reporting exclusive breastfeeding during their premenopausal years for 7–12 months. It was reported that breastfeeding was also associated with a significantly lower risk of early menopause independent of parity 14 . In our study, duration of breastfeeding weakly correlated with age at natural menopause.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In a prospective cohort study that included 108 887 women, risk of early menopause was lowest among those reporting exclusive breastfeeding during their premenopausal years for 7–12 months. It was reported that breastfeeding was also associated with a significantly lower risk of early menopause independent of parity 14 . In our study, duration of breastfeeding weakly correlated with age at natural menopause.…”
Section: Discussionsupporting
confidence: 54%
“…The association of parity with the timing of menopause has been previously examined in the literature. Lower parity and nulliparity was associated with higher risk of early menopause 9,13,14 . In our study, the mean age at menopause was found significantly higher in those reporting five or more births than P0 and P1‐4 groups.…”
Section: Discussionsupporting
confidence: 47%
“…Faye et al found similar results in Burkina Faso [12], as did Garrido-Latorre in Mexico [19] and Kaczmarek in Poland [10]. Christine et al in her multivariate model also found higher parity associated with a lower risk of early menopause [21]. The number of children per woman can influence the age of menopause.…”
Section: Discussionmentioning
confidence: 68%
“…43 Consistent with this, a lower risk of early menopause was associated with longer breastfeeding durations of 7 to 12 months (multiadjusted HR: 0.72; 95% CI: 0.62, 0.83) or 13 to 18 months (multiadjusted HR: 0.80; 95% CI; 0.66, 0.97), compared with less than 1 month of exclusive breastfeeding in the Nurses' Health Study II (NHS II) cohort. 44 Parenting/Childhood Experiences Lower cognitive scores in childhood were associated with earlier age at menopause and childhood intelligence was correlated with age at natural menopause. 43,45,46 Early-life violence may affect reproductive aging as demonstrated by the Avon Longitudinal Study of parents and children which found earlier age at menopause in victims of sexual abuse.…”
Section: Low Birth/early Childhood Weightmentioning
confidence: 99%
“…43 Consistent with this, a lower risk of early menopause was associated with longer breastfeeding durations of 7 to 12 months (multiadjusted HR: 0.72; 95% CI: 0.62, 0.83) or 13 to 18 months (multiadjusted HR: 0.80; 95% CI; 0.66, 0.97), compared with less than 1 month of exclusive breastfeeding in the Nurses' Health Study II (NHS II) cohort. 44…”
Section: Low Birth/early Childhood Weightmentioning
confidence: 99%